Advances in agronomy (Academic Press, 1995)
Volume 54 contains seven reviews covering key contemporary topics in the crop and soil sciences. The connections between agricultural practice and environmental impact are addressed in chapters on subsurface microbial ecology, herbicide-resistant field crops, and nitrification inhibitors. Also among this collection are reviews on the microbial reduction of iron, manganese, and other metals; acid tolerance of wheat; lentil breeding and production; and the use of apomixis in cultivar development. With this latest volume, Advances in Agronomy continues to be recognized as a prolific and first-rate reference by the scientific community. In 1993 Advances in Agronomy increased its publication frequency to three volumes per year, and will continue this trend as our breadth of agronomic inquiry and knowledge continues to grow.